Case report: Target and immunotherapy of a lung adenocarcinoma with enteric differentiation, EGFR mutation, and high microsatellite instability - Yang, Meiling; Yu, Pengli; He, Zhiyi; Deng, Jingmin (Frontiers in Immunology, 2024)
Background: Pulmonary enteric adenocarcinoma (PEAC) is a rare histological subtype of non-small cell lung cancer (NSCLC) with a predominant (>50%) enteric differentiation component. The frequency of high microsatellite instability (MSI-H) is very low in lung cancer. EGFR tyrosine kinase inhibitors and immunotherapy are standard treatment for NSCLC patients, but their effectiveness in lung adenocarcinoma with pulmonary enteric differentiation is unknown.Case presentation: This report describes a 66-year-old man who was initially diagnosed as metastatic lung adenocarcinoma with EGFR mutation based on pleural fluid. A lung biopsy was obtained after 17 months of first-line icotinib treatment.Histological analysis of biopsy samples and endoscopic examination resulted in a diagnosis of adenocarcinoma with enteric differentiation. Next-generation sequencing of 1021 genes showed EGFR E19del, T790M and MSI-H, while immunohistochemical assay showed proficient expression of mismatch repair (MMR) proteins. Consequently, the patient was treated with osimertinib and had a progression-free survival (PFS) of 3 months. He changed to receive chemotherapy with/without bevacizumab for 6.5 months. Then the patient was treated with one cycle of camrelizumab monotherapy and camrelizumab plus chemotherapy, respectively. The tumor continued to grow and the patient developed suffered pneumonia, pulmonary fungal infections and increased hemoptysis. He received gefitinib and everolimus and died 2 months later and had an overall survival of 30 months.In summary, our case describes a rare pulmonary enteric adenocarcinoma with EGFR sensitive mutation and MSI-H, responding to EGFR tyrosine kinase inhibitor and poorly benefiting from immune checkpoint inhibitor.